2023
DOI: 10.3390/plants12061348
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activities of Arnica montana Planta Tota versus Flower Extracts: Analytical, In Vitro and In Vivo Mouse Paw Oedema Model Studies

Abstract: Arnica montana is well known for its anti-inflammatory properties. While the anti-inflammatory activity of Arnica flowers (Arnicae flos) has been extensively studied, that of the whole plant (Arnicae planta tota) is less characterized. We compared the ability of Arnicae planta tota and Arnicae flos extracts to inhibit the pro-inflammatory NF-κB—eicosanoid pathway, using several in vitro and in vivo assays. We showed that Arnicae planta tota inhibited NF-κB reporter activation, with an IC50 of 15.4 μg/mL (vs. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Other natural products typically found in the flower-head are flavonoids such as quercetin and kaempferol, coumarins, and an essential oil [ 31 , 32 ]. A preparation with A. montana showed anti-inflammatory effects in vivo for arthritis [ 33 ]. In particular, helenalin seems to interact with many cysteine residues in a number of target proteins, modifying their activity, such as with NFkB and NFAT, two transcription factors orchestrating the inflammation pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Other natural products typically found in the flower-head are flavonoids such as quercetin and kaempferol, coumarins, and an essential oil [ 31 , 32 ]. A preparation with A. montana showed anti-inflammatory effects in vivo for arthritis [ 33 ]. In particular, helenalin seems to interact with many cysteine residues in a number of target proteins, modifying their activity, such as with NFkB and NFAT, two transcription factors orchestrating the inflammation pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Edema is one of the obvious indicators of inflammation and a key factor to take into account when assessing the anti-edematogenic and anti-inflammatory properties of a substance [ 74 ]. Carrageenan is an acknowledged pro-inflammatory agent that has been used to initiate acute inflammatory episodes upon injection into the footpad of rodents, and it well recapitulates the pathogenesis characteristics [ 75 , 76 ]. Carrageenan has been found to resist biodegradation due to its persistence within Kupffer cells for several months [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seed extract (50 mg.kg −1 for 2 months) decreased the plasma levels of inflammatory cytokines TNF-α, IL-8, IL-6, and IL-1β as well as erythrocyte concentration, ROS level, and lipid peroxidation, and fortified the activity of the main antioxidant enzymes [ 87 ]. It was reported that phenolic compounds are similar to NSAIDs in their ability to decrease the chemical mediators of inflammation [ 75 ]. We hypothesize that the increased and more varied content of bioactive substances in MMEx explains the higher anti-inflammatory activity by diminishing TNF-α, IL-1β, and COX targets or by blocking the NF-κB pathway and its messengers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing interest in this species and its possible industrial applications. Different bioactive compounds have been identified in AM, including sesquiterpene lactones, which are associated with anti-inflammatory properties, and phenolic compounds (mainly phenolic acids and flavonoids), known for their antioxidant and antimicrobial activities [2]. Nowadays, phenolic compounds are one of the most studied groups of bioactive compounds in plants, algae, and foods.…”
Section: Introductionmentioning
confidence: 99%